Water-based chemicals and technology for drilling, completion, and workover fluids - Fink, Johannes Karl (Gulf Professional Publishing is an imprint of Elsevier, 2015)
Oil and gas engineers today use three main factors in deciding drilling fluids: cost, performance, and environmental impact, making water-based products a much more attractive option. This book delivers all the background and infrastructure needed for an oil and gas engineer to utilize water-based products that benefit the whole spectrum of the well's life cycle. Helping to mitigate critical well issues such as formation damage, fluid loss control, and borehole repair, more operators demand to know the full selection of water-based products available to consistently keep a peak well performance. Topics include: chemical index of structural formulas; types, special additives, and chemical compatibilities of products available; waste disposal techniques, including management of produced water, a component mandatory to hydraulic fracturing operations. -- Edited summary from book.
Keywords: Drilling muds.; Drilling muds -- Additives.; Water.; elektronické knihy; electronic books